Cationic surfactant-directed structural control of NaCl crystals from evaporating sessile droplets. Issue 1 (8th December 2021) - Dewangan, Jayant K.; Basu, Nandita; Chowdhury, Mithun
Abstract : Competitive surface adsorption of anionic counterions control the morphology during the evaporative crystallization of saline (NaCl) microdroplets containing a cationic surfactant (CTAB). Abstract : We report morphological regulation of NaCl (sodium chloride) crystals through the evaporative crystallisation process of microdroplets containing a cationic surfactant CTAB (cetyltrimethylammonium bromide). Various fascinating evaporative salt morphologies are observed using different combinations of salt ( C NaCl ) and surfactant ( C CTAB ) concentrations. Each observed morphology is carefully explained by the interplaying physical phenomena, such as crystallisation, micellisation, evaporative dewetting, and surface adsorption of anionic couneterions. Salt morphologies are investigated for low ( C NaCl = 0.1 (M)), intermediate ( C NaCl = 0.5 (M)) and high ( C NaCl = 2 (M)) concentrations, whereas surfactant concentrations are varied four orders of magnitudes (from 0.0001 (M) to 0.1 (M)). Interestingly, we observe a threshold in C CTAB at 0.001 (M), beyond which the peripheral rings of dried deposits are found to be composed of CTAB for C NaCl = 0.1 (M), while the same is seen to be made up of NaCl for C NaCl = 2 (M). We have explained the morphological evolution by the process of competitive surface adsorption phenomenon between Cl − and Br − counter ions. Such a detailed study of saline droplet crystallisation in the presence of a cationic surfactant underpins the fundamental understanding of the crystallisation process. In addition, it may further impact application sectors where crystallisation of saline solution plays an important role, especially in the presence of additives.